Measuring and analyzing the relationship between the fiscal policy indicators and the bank stability index in Iraq for the period 2010-2016 using the ARDL model. - صالح عمار حمد; حسن ضياء عبد الرزاق (Journal of Economics and Administrative Sciences, 2018)
The importance of this research is to clarify the nature and the relationship between the indicators of financial policy and banking stability in Iraq, as well as to find a composite index reflects the state of banking stability in Iraq in order to provide an appropriate means to help policymakers in making appropriate decisions before the occurrence of financial crises. Hence, the problem of research is that the fiscal policy has implications for the macro economy and does not rule out its impact on banking stability. Moreover, the central bank does not possess a single indicator that reflects the stability of the banking system, rather than the scattered indicators that depend on determining the stability of banking through changes Relative to those indicators. The paper used quarterly data for the period 2010-2016. It apply the ARDL model to examine the hypothesis that financial policy had an effect on banking stability through the proposed aggregate index of banking stability. The paper found that government’s borrowing by treasury bills enhance the banking stability and this Positive relationship emerged because of the classification of the treasury bills within the liquidity components during the period of the study (2016-2010). This is done if there is a capacity of fiscal policy to repay the debt, but if the debt exceeded the capacity of the government to repay will have a negative impact on the banking stability. The paper suggested that the fiscal policy must build sovereign fund for the purpose of exploiting the surplus in fiscal policy in times of prosperity and use them in times of crisis in which the fiscal policy needs funds to carry out its duties and the purpose of not to crowd out the economic units especially the banking system through continuous borrowing. This may lead to a decline in the ability of the government to repay debts. The Central Bank of Iraq should adopt than aggregated index of banking stability, which is a mean for forecasting early warning of banking crisis.